Digitization of Bulgaria’s ethnographic archival heritage (Research Announcements "Heritage BG", 2023)
The text was conceived as an account of the plans of the AIEFEM team to modernize, to make adequate to modern technical and scientific standards and to promote its archival heritage. Despite the poor conditions of preservation of the archival materials until now, the collections are enjoying significant interest and attention by different social and professional groups. The purpose of the described digitization is to enable the worldwide dissemination of valuable cultural visual data particularly of a preindustrial period and practices, less known as models of cultural manipulation. References:Levski, D. (2017). Tsifrovi svetlinni senzorni matritsi – ot erata na dinozavrite do dnes. Balgarska nauka, 96.Parvanov, I. (2021). Digitalen atlas na balgarskia tantsov folklor. Zoni na razprostranenie spored terennite prouchvania v etnohoreologiyata. PhD dissertation, manuscript, Sofia: IEFSEM.Brennen, S., & Kreiss, D. (2014). Culture Digitally – Digitalization and Digitization. Retrieved from http://culturedigitally.org/2014/09/digitalization-and-digitization/ (accessed 05.03.2022).Butterworth, J., Pearson, A., Sutherland, P., & Farquhar, A. (2018). Remote Capture: Digitising Documentary Heritage in Challenging Locations. Cambridge, UK: Open Book Publishers.DIN–German national standard. (2019). DIN SPEC 15587 – Recommendations for digitization of cinematographic film. Retrieved from European Standards: https://www.en-standard.eu/din-spec-15587-recommendations-for-digitization-of-cinematographic-film/ (accessed 22.04.2023).Fulton, W. (1997-2019). A few scanning tips. Retrieved on November 03, 2019, from https://www.scantips.com/chap3c.html (accessed 30.04.2023).Iraci, J. (2017). The Digitization of VHS Video Tapes. Retrieved from Canadian Preservation Institute: https://publications.gc.ca/collections/collection_2018/pch/CH57-3-1-31-2016-eng.pdf (accessed 19.04.2023).Iraci, J., Hess, R., & Flak, K. (2017). The Digitization of Audio Tapes. Retrieved from Canadian Conservation Institute: The Digitization of Audio Tapes – Technical Bulletin 30 – Canada.ca (accessed 19.04.2023).ISO/TR 13028:2010. Retrieved from International Organization for Standardization: https://www.iso.org/standard/52391.html (accessed 20.04.2023).Johnson. (2021). Preservation Digitization Standards for the Digitization of Physical RNA records. Retrieved from National Archives of Australia: https://www.naa.gov.au/sites/default/files/2022-01/Preservation-Digitisation-Standards-2021.pdf (accessed 20.04.2023).Leggett, E. (2021). Digitization and Digital Archiving: A Practical Guide for Librarian. Rowman & Littlefield.Microsoft Docs. (2017). Types of Bitmaps. Retrieved on 10.11.2019 from https://docs.microsoft.com/en-us/dotnet/framework/winforms/advanced/types-of-bitmaps?view=netframework-4.7.2 (accessed 22.04.2023).Pushkar, O., & Sibilyev, K. (2011). Information Systems and Technologies. Summary of Lectures. Retrieved on October 12, 2019, from http://www.repository.hneu.edu.ua/handle/123456789/5879 (accessed 25.04.2023).Stark, H. (1982). Application of Optical Fourier Transforms. New York: Academic Press.Villarreal. (2020). The Use of 3D Apparel Simulation Software for Digitizing Historic. PhD dissertation, manuscript, NC State University Libraries. Retrieved from https://repository.lib.ncsu.edu/bitstream/handle/1840.20/38170/etd.pdf?sequence=1&isAllowed=y (accessed 22.04.2023).Zigouris, P. (2021). Contemporary Methods of Digitization. Athens: Panagiotis Zigouris.
Keywords: scientific ethnographic archive; digitization; endangered collections